Ezour-Védam: Europe’s Illusory First Glimpse of the Veda - Killingley, Dermot (Religions of South Asia, 2008)
A text in french with the title Ezour-Védam was proclaimed by Voltaire as a sample of ancient indian wisdom. it was soon suspected of coming from a missionary source, and this view has prevailed. in 1817, francis ellis studied and described the collection of texts in Pondicherry to which it belonged, and in 1984 ludo Rocher published the french text with a study of its possible origins. the present article examines the text again, relating it to european thought and Jesuit missionary methods. its reception by Voltaire and others, the meaning of the title, the common description of it as a forged Veda, and a misunderstanding concerning Rammohun Roy, are also discussed.